An Improvised Pulmonary Telerehabilitation Program for Postacute COVID-19 Patients Would Be Feasible and Acceptable in a Low-Resource Setting - Bickton, Fanuel Meckson (Am J Phys Med Rehabil, 2021)
Postacute COVID-19 patients are at risk of long-term functional impairment, and the rehabilitation community is calling for action preparing for a “tsunami of rehabilitation needs” in this patient population. In the absence of standard guidelines and local evidence, a 3-wk pulmonary telerehabilitation program was successfully delivered to a postacute severe COVID-19 patient in Malawi. The patient experienced persistent dyspnea and fatigue, with a remarkable impact on his health status. On the final assessment, all his respiratory severity scores had fallen by more than their thresholds for clinical significance. He reported no continued or new complaints, was walking longer distances, had returned to work, and was discharged from follow-up. Our case shows that an improvised pulmonary telerehabilitation program for postacute COVID-19 patients could be feasible and acceptable in a low-resource setting. Benefits include reducing risk of transmission and use of personal protective equipment.